Impact of the COVID-19 pandemic on suicide rates in Japan through December 2021: An interrupted time series analysis - Eiji Yoshioka; Sharon J.B. Hanley; Yukihiro Sato; Yasuaki Saijo (Elsevier, 2022)
Summary: Background: The COVID-19 pandemic is negatively impacting mental health globally. While increased social cohesion may have initially decreased suicide risk, there are few reports on the long-term impact. We examined the impact of the pandemic on suicide by gender and age through December 2021 in Japan. Methods: We analyzed trends in monthly suicide rates by age and gender from January 2016 to December 2021 using provisional mortality data in an interrupted time series analysis. We also considered linear trends in the pre-pandemic period and seasonal variations. Pandemic onset was defined as from April 2020. Estimated excess deaths by suicide that occurred during the pandemic were calculated. Findings: Excess number of suicide deaths during the pandemic period was estimated to be 1208 for men and 1825 for women. While there was no statistically significant increase in suicide rates overall for both men and women during the pandemic compared to the pre-pandemic, age-specific analyses showed a statistically significant increase in men 20-29 and 40-49 years, and in women of all age groups, except those under 20, 40-49 and over 80 years. Interpretation: The COVID-19 pandemic has had a negative impact on suicide rates in Japan and the impact is most pronounced in women and younger age groups. Subgroup analyses are needed, with a particular focus on those considered to be vulnerable and at increased suicide risk. Funding: A Grant-in-Aid for scientific research from the Ministry of Education, Culture, Sports, Science and Technology of Japan (Award Number 21K10462).